1988
DOI: 10.1007/bf01787820
|View full text |Cite
|
Sign up to set email alerts
|

Social construction or causal ascription: Distinguishing suicide from undetermined deaths

Abstract: Summary. This study reports findings of the first Scottish comparison between suicide and undetermined deaths on a number of sociodemographic and psychiatric variables, and also in relation to the method of death. Logistic regression analysis confirmed that method was the most powerful and significant discriminator (88% of 'active' deaths were labelled suicide compared to only 54% of drowning) and also pointed to an interaction between gender and age. The two types of death could not be differentiated by marit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 12 publications
0
22
0
1
Order By: Relevance
“…33 Apparently non-random across decedent demographics and methods, 34,35 undercounting suicide likely distorts rates and differentials. Among factors plausibly exacerbating suicide case ascertainment in the twenty-first century are the secular decline in the combined clinical and forensic autopsy rate, 36,37 rare use of psychological autopsies in helping medicolegal authorities resolve the manner of death in cases of equivocal intent, 38 and extant disparities and underresourcing of the emergency healthcare 39,40 and death investigation systems.…”
Section: Discussionmentioning
confidence: 99%
“…33 Apparently non-random across decedent demographics and methods, 34,35 undercounting suicide likely distorts rates and differentials. Among factors plausibly exacerbating suicide case ascertainment in the twenty-first century are the secular decline in the combined clinical and forensic autopsy rate, 36,37 rare use of psychological autopsies in helping medicolegal authorities resolve the manner of death in cases of equivocal intent, 38 and extant disparities and underresourcing of the emergency healthcare 39,40 and death investigation systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, this may be due partly to the requirement of strong corroborative evidence (40) and partly to social pressures, such as familial stigma or concerns about life insurance reimbursement (41). We therefore examined firearm-related suicides (ICD-9 code E955) separately for 2 reasons: Firearms are generally more lethal than other means (42, 43), and firearm-related deaths are less likely to be classified as being from undetermined causes than deaths related to more passive means (4446), which is the category most susceptible to misclassification (47). Consistent with the latter, although only 3% of deaths due to injuries in the United States are described as deaths from undetermined causes, the percentage of firearm-related deaths described as being from undetermined causes is smaller by an order of magnitude (0.2%) (48).…”
Section: Methodsmentioning
confidence: 99%
“…This is supported by the fact that the trends for recorded suicide and suicide and undetermined deaths have followed a similar pattern (Charlton et al, 1992). Platt et al (1988) have shown that the main difference between open verdicts and recorded suicides, in the community, is the method of killing, with passive methods (e.g. drowning) being less likely to receive a suicide verdict.…”
Section: Introductionmentioning
confidence: 98%